Synthesis of P- and S-Stereogenic Compounds via Enantioselective C–H Functionalization - Qian, Pu-Fan; Li, Jun-Yi; Zhou, Tao; Shi, Bing-Feng (Synthesis, 2022)
Transition metal-catalyzed enantioselective C–H functionalization has emerged as an efficient and powerful strategy to access various chiral molecules. Recently, this strategy has also provided a complementary pathway to the construction of P- and S-stereogenic compounds. In this short review, we summarize the development and applications of various catalytic systems: Pd(II)/mono-N-protected amino acids (MPAA), Pd(0)/trivalent phosphorus chiral ligands, chiral cyclopentadienyl-ligated metal catalysts [CpxM(III)] (M = Rh, Ir), half-sandwich d6 Ir(III) and Ru(II) with a chiral carboxylic acid (CCA) ligand, Ir(I)/chiral bidentate boryl ligand, and Ir(I)/chiral cation, for accessing these chiral compounds via enantioselective C–H functionalization. 1 Introduction2 Pd(II)/Mono-N-protected Amino Acids3 Pd(0)/Trivalent Phosphorus Chiral Ligands4 Chiral Cyclopentadienyl-Ligated Metal Catalysts [CpxM(III)] (M = Rh, Ir)5 Half-sandwich d6 Ir(III) and Ru(II) with a Chiral Carboxylic Acid (CCA) Ligand6 Ir(I)/Chiral Bidentate Boryl Ligand7 Ir(I)/Chiral Cation8 Conclusion and Outlook
Keywords: enantioselectivity; C–H functionalization; P- and S-stereogenic compounds; chiral ligands; transition metals